Model of Using E-Prescription Technology to Improve Patient Waiting Time Efficiency at The Outpatient Pharmacy of RSUD Dr. H. Jusuf SK of Tarakan City - Muhadir, Muhadir; Wahyudi, Bayu; Bagenda, Wahyuddin (CV. Civiliza Publishing, 2025)
This study aims to assess the utilization of e-prescription technology in improving the efficiency of patient waiting times at the outpatient pharmacy of RSUD Dr. H. Jusuf SK, Tarakan City. Using a quantitative approach with a cross-sectional design, this research analyzes the relationship between the use of e-prescription systems and the efficiency of patient waiting times. Data were collected at a specific point in time from the outpatient pharmacy installation, involving a sample of 98 patients selected using the Slovin formula and purposive sampling technique. Inclusion criteria included patients receiving prescriptions at the outpatient pharmacy, who had used or were using the e-prescription/manual system, were willing to participate, and aged between 18–65 years. Data collection methods included direct observation, document review, and questionnaires using a Likert scale. The results showed that the implementation of e-prescriptions significantly improved patient waiting time efficiency, with an average reduction of approximately 30 minutes for both compounded and non-compounded prescriptions compared to manual prescriptions. However, despite the significant reduction, the waiting times for compounded drugs (average 90 minutes) and ready-made drugs (average 82 minutes) still did not meet the minimum service standards set by the Indonesian Ministry of Health Regulation No. 79/Menkes/2016 (i.e., 30 minutes for ready-made drugs and 60 minutes for compounded drugs). As many as 84% of prescriptions did not yet meet these minimum standards. Identified inhibiting factors included prescription accumulation during peak patient hours, the habit of printing e-prescriptions onto paper before processing, the verification process within the BPJS application system, and occasional errors in the e-prescription system.